The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1042/bst20180250
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid transporters in the regulation of insulin secretion and signalling

Abstract: Amino acids are increasingly recognised as modulators of nutrient disposal, including their role in regulating blood glucose through interactions with insulin signalling. More recently, cellular membrane transporters of amino acids have been shown to form a pivotal part of this regulation as they are primarily responsible for controlling cellular and circulating amino acid concentrations. The availability of amino acids regulated by transporters can amplify insulin secretion and modulate insulin signalling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 253 publications
(279 reference statements)
2
32
0
Order By: Relevance
“…However, large variations of amino acid concentrations have been noted (Taylor and Smith, 1987;Meier et al, 2002) between oocyte stages, time post-surgery, and ionic incubation conditions. The method developed here can also be used to investigate amino acid signaling, the components of which are highly conserved in multicellular eukaryotes (Panchaud et al, 2013;Saxton and Sabatini, 2017;Tatebe and Shiozaki, 2017;Javed and Fairweather, 2019). Our results support the concept of SNAT2 as a transceptor (Pinilla et al, 2011), because mTORC1 activation was observed at time points where cytosolic leucine was barely increased.…”
Section: Discussionsupporting
confidence: 77%
“…However, large variations of amino acid concentrations have been noted (Taylor and Smith, 1987;Meier et al, 2002) between oocyte stages, time post-surgery, and ionic incubation conditions. The method developed here can also be used to investigate amino acid signaling, the components of which are highly conserved in multicellular eukaryotes (Panchaud et al, 2013;Saxton and Sabatini, 2017;Tatebe and Shiozaki, 2017;Javed and Fairweather, 2019). Our results support the concept of SNAT2 as a transceptor (Pinilla et al, 2011), because mTORC1 activation was observed at time points where cytosolic leucine was barely increased.…”
Section: Discussionsupporting
confidence: 77%
“…Their expression in the HFCS group was significantly decreased compared with that in the control group ( Figure 5 A,B). Depending on the metabolic and nutritional status, amino acids, such as glutamine and glutamate, act as modulators of nutrient disposal, and play a role in regulating blood glucose through interaction with insulin signaling [ 28 ]. The mRNA expression of the amino acid transporter SLC38A3, and of the glutaminolysis enzymes glutaminase ( Gls ) and glutamate dehydrogenase 1 ( Glud1 ), did not differ between the two groups ( Figure 5 C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Both glutamate and glutamine provide reducing equivalents for the production of NADH in the TCA cycle and ultimately for the synthesis of ATP to facilitate glucose-stimulated insulin secretion via the closure of ATP-sensitive potassium channels [ 28 , 58 ]. Glutamine is transported into β-cells by transporters, such as SLC38A3 [ 28 , 59 , 60 ]. Glutamine is converted to glutamate by Gls and then to α-ketoglutarate by Glud.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the availability of amino acids or peptides is regulated by transporters, whose enhancement was also beneficial for insulin signaling modulation in various tissues, including the small intestine, pancreatic -islet cells, liver, and skeletal muscle. [47] Diabetes leads to poor permeability of the intestinal epithelial barrier and impairs amino acids or peptides transporter functions, thus resulting in low nutrients bioavailability, including peptides and amino acids. [47,48] Amino acid supplementation was demonstrated to ameliorate the damaged permeability of the intestinal barrier, improve the amino acids or peptides transporter function, and then result in the increased amino acid and peptide bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…[47] Diabetes leads to poor permeability of the intestinal epithelial barrier and impairs amino acids or peptides transporter functions, thus resulting in low nutrients bioavailability, including peptides and amino acids. [47,48] Amino acid supplementation was demonstrated to ameliorate the damaged permeability of the intestinal barrier, improve the amino acids or peptides transporter function, and then result in the increased amino acid and peptide bioavailability. [49,50] As such, higher levels of amino acids generated by the protein isolate from the cooked foxtail millet via hydrolysis in vivo may better alleviate the impaired permeability of the intestinal epithelial barrier, enhance the amino acid or peptides transporter function, and then increase the bioavailability of peptides and amino acids, which contributes to glucose metabolism modulation ultimately.…”
Section: Discussionmentioning
confidence: 99%